The correlates of self-concept, aspirations and academic achievement - Chan, Chan Hoa (1982)
This study attempted to find out whether there were any significant correlations among student's self-concept, his aspirat ions and academic achievement. Two measures of self concept were used, viz., student's self-concept as a learner and teacher's perception of student's self-concept as a learner. Data on these variables were obtained by means of Waetjen's 'Self-concept As A Learner Scale' and Florida Key (A Scale to infer Learner Self-concept) respectively. Variables of aspirations pertaining to the students also included educational aspiration, occupational aspiration, educational expectation, occupational expectation and parental aspiration for the child. Data on these variables were collected by using another set of questionnaire. Academic achievement referred to the students' performance in the Malaysian Certificate of Education Examination. A comparison was also made between the boys and girls as well as the two levels of self-concept in terms of all the variables under study.